2017
DOI: 10.1080/1331677x.2017.1311233
|View full text |Cite
|
Sign up to set email alerts
|

Audit fees and the salience of financial crisis: evidence from Slovenia

Abstract: The financial crisis that has recently affected the EU economies created a research setting that enabled the examination of the effect of the financial crisis outbreak on audit fees by studying the deviation of audit fees in the post-crisis period as compared to the pre-crisis period. Financial crisis represents a setting that is tightly related to the concepts of audit risk and liability, where higher audit fees can be expected to account for increased audit engagement. The article identifies the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
(82 reference statements)
0
14
0
1
Order By: Relevance
“…Since AB_LNFEES are calculated as the difference between audit fees and 'normal' or 'expected' audit fees, we first estimate the expected audit fees. Prior literature (Gand ıa & Huguet, 2018;Sundgren & Svanstr€ om, 2013;Zaman Groff et al, 2017) shows that audit fees depend on company and auditor characteristics, which can be classified into five groups: i) auditor characteristics, ii) company size, iii) company complexity, iv) company risk and v) other characteristics. Previous literature has shown that large auditors show an audit fee premium (Clatworthy et al, 2009; Sundgren & Svanstr€ om, 2013), so we include LARGE and BIG as explained before.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AB_LNFEES are calculated as the difference between audit fees and 'normal' or 'expected' audit fees, we first estimate the expected audit fees. Prior literature (Gand ıa & Huguet, 2018;Sundgren & Svanstr€ om, 2013;Zaman Groff et al, 2017) shows that audit fees depend on company and auditor characteristics, which can be classified into five groups: i) auditor characteristics, ii) company size, iii) company complexity, iv) company risk and v) other characteristics. Previous literature has shown that large auditors show an audit fee premium (Clatworthy et al, 2009; Sundgren & Svanstr€ om, 2013), so we include LARGE and BIG as explained before.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, previous literature shows that the use of audit-based variables is often affected by endogeneity problems (Huguet & Gand ıa, 2014;Kim et al, 2011). Prior literature has tackled these problems by using a fixed-effects (FE) regression estimation (Gand ıa & Huguet, 2020; Kim et al, 2011;Zaman Groff et al, 2017). Some authors (Francis, 2011;Lennox et al, 2012;Wintoki et al, 2012) suggest the use of a fixed-effects (FE) regression estimation, which can alleviate the potential selfselection bias and omitted variables problem as long as the unobserved source of endogeneity is time-invariant.…”
Section: Methodsmentioning
confidence: 99%
“…Although some papers try to mitigate the endogeneity problems using a Heckman two-stage approach (Pittman & Fortin, 2004;Cano Rodr ıguez et al, 2016), literature shows that Heckman results depend on a proper selection of the instrumental variables, and results lack on robustness, being even more biased and unreliable than OLS estimations (Clatworthy, Makepeace, & Peel, 2009;Larcker & Rusticus, 2010;Lennox, Francis, & Wang, 2012). Some authors (Francis, 2011;Lennox et al, 2012;Wintoki, Linck, & Netter, 2012) suggest that the use of a fixed-effects (FE) regression can mitigate the potential self-selection bias and omitted variables problems as long as the unobserved source of endogeneity is timeinvariant, and this approach has been used by previous literature (Huguet & Gand ıa, 2016;Kim et al, 2011;Zaman Groff, Trobec, & Igli car, 2017). For this reason, we estimate Equations (1a) and (1b) using a firm FE regression procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The model estimates a linear regression in which LNFEES is function of a series of determinants of audit fees, which have been tested by previous literature (Gand ıa & Huguet, 2018;Zaman Groff et al, 2017) and control for auditor size, company size (natural logarithm of total assets, natural logarithm of net turnover and natural logarithm of number of employees), company complexity (proportion of inventory and receivables over total assets, acquisitions, proportion of intangibles, reporting of unusual items in the income statement, use of simplified GAAP, number of subsidiaries, and whether the company belongs a group), company risk (leverage, changes in leverage, company growth, profitability, presence of negative earnings, interaction between profitability and negative earnings, current ratio, quick ratio, solvency ratio and changes in the solvency ratio), presence of modified audit reports, year-end date, if the company is located in Madrid or Barcelona, and the age of the company. The model also includes year and industry dummies.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive literature reveals that the audit fees are positively related to risk, as evinced in the papers by Xu et al (2013), Zhang and Huang (2013), Alexeyeva and Tobias (2015), and Groff et al (2017). That is, higher client risk may expose the auditor.…”
Section: Riskmentioning
confidence: 97%